Scrub Typhus in Children - Zainab, Madiha; Gupta, Atul Kumar; Guha, Suparna (Journal of Nepal Paediatric Society, 2018)
Introduction: Scrub typhus is an acute febrile illness caused by infection with rickettsial bacilli Orientia tsutsugamushi. This was a retrospective observational study to study the clinical profile of paediatric scrub typhus, its associated complications and response to treatment Material and Methods: Record files of all patients diagnosed with positive Weil felix (OXK>1:80) and Scrub IgM positive over a period of one year were analysed. Total of 10 cases were diagnosed as scrub with median age of presentation 4.1 years. Results: Fever was present in all followed by pain abdomen (50%), rash. Anaemia (90%), lymphadenopathy (70%) hepatomegaly (100%), Leukopenia was present in those cases with fever <1 week while leucocytosis was found thereafter. Most common complication were hepatitis (100%) shock (50%), acute kidney injury (AKI) 30%, DIC in 20% cases. Secondary HLH was found in 20% and pancarditis in one case. All the cases showed dramatic response to doxycycline. Conclusion: So a high index of suspicion is required to diagnose scrub and early initiation of treatment is essential to prevent mortality from the disease.